Jejak Budaya Musyawarah, Bentuk Demokrasi Masyarakat Minangkabau - Eny Christyawaty; Nenggih Susilowati (Berkala Arkeologi Sangkhakala, 2010)
AbstractMinangkabau society always strives for a peaceful and prosperous life. Since long time ago, the community is implementing democratic values. These values are reflected in the archaeological remains associated with the activities of deliberation and the tradition that lasted until now. In making decisions for common interests, people tend to give priority to said agreement despite differences of opinion are also valued.